Expected benefits of snap bean research for the developing world - Henry, Guy (International Center for Tropical Agriculture, 1990)
In an assessment of the possible benefits to consumers and producers from snap bean research, four different technologies are proposed and their impact analyzed. Benefits are measured by using a welfare analysis and calculating the internal rate of return under different assumptions. The range of total benefits from the four technologies is between US$12 million and US$99 million a year. The most benefits would be generated by Integrated Pest Management technologies and adoption of insect and disease resistant snap bean varieties. Even when costs are doubled and impact halved, the IRR on these technologies is higher than 40 percent. (AS)